Recyclable Waste Forecasting With Statistical Assessment of Numerical Models - et. al., Sujinna Karnasuta, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aimsstudy on the data collection and forecasting in the recycle wastes of the 2 green schools are Prachaniwetschool and Sainamtip school, from 2018 to 2020 through these 3 years. The large Prachaniwetschool under Bangkok Metropolitan Administration (BMA) and The large Sainamtip school under Ministry of Education that had engaged in project of the green school locating on Bangkok city.The recycle wastes in 4 categories as recycling plastic, recycling glass, recycling paper and recycling can, compare between Prachaniwet school and Sainamtip school in range of 6 months.The statistical analysis from the data collection with 4 forecasting technics, are Moving average, Weight moving average, Simple exponential smoothing, Holt’s exponential smoothing.The recycling waste from both Prachaniwet school and Sainamtip school in 4 categories in range of 6 months from 2018 to 2020. The most recycling waste is plastic, which has a seasonal effect due to semester start. The others recycling waste are glass, paper, and can seem to be vanish after September of 2019. Recycle glass appeared in June of 2018 then emerging in September of 2018 then drop in March 2019 which is the closing semester period. The amount of recycling waste that produced from both Prachaniwetschool and Sainamtip school 4 categories from 2018 to 2020. Waste plastic is the biggest among recycle waste in these 3 years, about 210 kilograms. Then, recycled glass appears to be 20 kilograms. Recycled paper waste and recycled can waste are 5 kilograms and 8 kilograms, respectively. The comparison in 4 categories between Prachaniwetschool and Sainamtipschool.Sainamtip school seem to have recycling plastic waste, recycling glass waste, and recycling can waste more than Prachaniwet school. In recycling paper waste, Prachaniwetschool seem to have more than Sainamtip school. The 4 forecasting techniques for 4 types of recycling wastes in Prachaniwet school in 2021 Prachaniwet school in 2021 with Moving average, Weight moving average, Simple exponential smoothing, Holt’s exponential smoothing, indicate that the recycling plastic has seasonal effect because the semester starts, the forecasting in 2021 for recycling plastic drop in March and November. And the others 3 recycling wastes lines seem to lay on 0 kilograms and then emerging about 2 months and then drop to 0 kilograms. The forecasting techniques for 4 types of recycling wastes in Sainamtip school in 2021 with Moving average, Weight moving average, Simple exponential smoothing, Holt’s exponential smoothing, indicate that the forecasting line for Sainamtip school moving like forecasting line in Prachaniwet school. The research result benefits from The forecasting techniques of this research with the Moving average, the Weight moving average, the Simple exponential smoothing, the Holt’s exponential smoothing can be used to prepare for what will happen in the future, gain the valuable in insight, and thee result from prediction methods could decrease cost for the environmental management on the green schools on the recycle waste..